Pabaltijo respublikų bibliotekinių ryšių raida - Motiekienė, Vilija (Knygotyra, 1988)
In this article, the main periods of the development of interlibrary relationships between Latvia, Lithuania, and Estonia are characterized. It is suggested that official interlibrary relationships began in 1930 with the organization of the first conference for librarians. Collaboration between the largest scientific libraries of the Baltic republics emerged in the 1950s. However, during the years 1945-1957, the relationships could be characterized as spontaneous, unplanned, and covering only a few areas of library work. Since the 1960s, these relationships became more intensive, with new forms of collaboration being applied. In the 1960s-1970s, traditional forms of interaction between libraries of the same type were implemented in practice. The most intensive relationships were developed between technical libraries. Although recently a unified coordination of this relationship does not exist, which is why the potential for collaboration is only partially utilized, the interlibrary commissions and methodological centers are the main institutions for the further development of interlibrary coordination.